Sociological approach to the study of Russia’s image in the Indonesian media - V. L Muzykant; Panca Syurkani (RUDN journal of Sociology)
The concept of a multipolar world is based on the idea of balance and equal rights for every country in the international world, and this concept was outlined in the Russian Foreign Policy Concept already in 2000. On several occasions, the President of Russia campaigned for a multipolar world order, which can be seen in some news reports in the Indonesian media. The sociological interpretation of the image is based on the descriptive qualitative framing analysis aimed at identifying how an event is understood and framed by the media. The authors collected the media data and conducted an analysis that allowed to make the following conclusions: first, a multipolar world is a concept that based on the idea of balance and equality; thereby, the geopolitical model of a multipolar world order is to replace the existing paradigm dominated by one civilization which extends throughout the world under the slogans of globalization, Westernization, Americanization, universalization, standardization and liberalization. Second, the image of Russia in the Indonesian media in relation to the multipolar world order creates the representation of the country as the one that encourages other states experiencing rapid growth to assert their sovereignty and defend their national interests, traditions and culture. Another image of Russia implies the same accent on the presence of countries experiencing free rapid development as confirming that the contemporary world is no longer under the influence of just one country or one pole, because every country has the same sovereign rights. Thus, Russia’s position as presented in the Indonesian media certainly finds the approval and support of the Indonesian society.